Tumor-mesenchymal stem cell interactions: therapeutic implications for epithelial ovarian cancer - Piché, Alain (Translational Cancer Research, 2018)
Epithelial ovarian cancer (EOC) is the most common cause of gynecological cancer-related death (1). When compared to most solid tumors, EOC has a distinct mechanism of dissemination. Cells detach from the primary tumor and aggregate in peritoneal fluid to form free-floating multicellular spheroids, which then travel through the peritoneal fluid at distant sites onto the mesothelial lining where metastatic outgrowth occurs (2). Because this process is clinically silent, most women (~70%) present with metastasis throughout the peritoneal cavity.